Religion in the work of Frantz Fanon - Settler, Federico (Department of Religious Studies, 2014)
This thesis explores Frantz Fanon's engagement with religion, and its impact on his theories of race and racism. As a cultural theorist and political activist with strong Marxian-humanist sympathies, Fanon asserted that, as an irrational force, religion anaesthetised the oppressed and inhibited the recovery of the black self. In this study I draw on critical and analytical work in the fields of religion, African studies, and postcolonial theory to interrogate the significance of the black body in the production of his aesthetic of transformation. To understand Fanon's engagements with religion I examine the social and political contexts of his native Martinique and his adopted Algeria, both countries which are defined by strict social and religious hierarchies. Through this focus on his engagement with Christianity, Islam and indigenous traditions in both Martinique and Algeria I argue that, while Fanon was ambivalent about the usefulness of religion in the anti-colonial struggle and the recovery of the black self, he nonetheless came to recognise the role of religion in producing narratives of the sacred that would cohere and motivate the colonized in their struggle against racist oppression. Finally, I argue that Fanon circumvents his ambivalence towards religion by elevating the significance of the enslaved and colonized body, as a sacred instrument of revolt and recovery. This thesis concludes that it is only through the production of such narratives of the sacred that Fanon is able to expel religion from the recovery of the black self and the inauguration of the new nation, while retaining traces of the sacred in his aesthetic of transformation.